WOMEN’S VIEW OF UKRAINIAN SOCIETY IN 1917–1921 IN MEMORIES OF CONTEMPORARIES (Південний архів (історичні науки), 2022)
The purpose of the article is to analyze the memoir literature of women who were contemporaries and active figures of the era of the Ukrainian Revolution, as a source for studying the state of society at that time. The application of the principles of scientific objectivity, historicism, systematicity and general scientific (analysis and synthesis, content analysis, generalization) and special-historical (historical-typological, historical-prosopographical, source heuristics) methods made it possible to identify, systematize, analyze and summarize information about memoir sources authored by women, contemporaries of the Ukrainian revolution. The sources were the memoirs of the leading contemporaries of the Ukrainian revolution. Among them are social and political activists, scientists, cultural figures: S. Rusova, Z. Mirna, N. Surovtsova, K. Antonovych, H. Pekarchuk, G. Sovacheva, H. Kononenko, T. Mykhailivska-Tsymbal, N. Polonska- Vasylenko. The result of processing women’s memories was the identification of their informative potential about revolutionary transformations in 1917–1921. Conclusions. Women’s memoirs are different in scope, time and place of writing, style and emotionality, but they are an important historical source for studying the society of the Ukrainian Revolution of 1917–1921. The memoirs convey the personal attitude of the female authors to political transformations, their impact on people, make it possible to understand what was the woman’s opinion and assessment of everything that was happening. The source sample testifies that women were actively involved in work in all spheres of life during the national liberation struggle of Ukrainian society in 1917–1921. They worked in the government, formed women’s public organizations, wrote books and textbooks, served in the army, and worked in universities, schools, theaters, hospitals. At the same time, the female part of society continued to arrange a personal life, take care of the household and raise children. Therefore, their life experience, recorded in the memoir literature, will allow us to consider the Ukrainian society of the revolutionary era of 1917–1921 from an unconventional point of view.
Keywords: sources of personal origin, memories, revolutionary era, woman, reflection.